Post-dengue acute disseminated encephalomyelitis: A case report and meta-analysis - Kamel, Mohamed Gomaa; Nam, Nguyen Tran; Han, Nguyen Huu Bao; El-Shabouny, Abd-Elaziz; Makram, Abd-ElRahman Mohamed; Abd-Elhay, Fatma Abd-Elshahed; Dang, Tran Ngoc; Hieu, Nguyen Le Trung; Huong, Vu Thi Que; Tung, Trinh Huu; Hirayama, Kenji; Huy, Nguyen Tien (PLOS Neglected Tropical Diseases, 2017)
Author summary We presented a 13-year-old girl of ADEM following dengue infection. She was totally alert and had a low grade of fever with no focal neurologic deficits, on admission. We revealed that the prevalence of either ADEM or all neurological disorders among dengue patients was not too rare. Moreover, we found that the most common manifestation of ADEM was altered sensorium/consciousness followed by seizures and urination problems then vision problems. These manifestations should be considered in the diagnosis and management of dengue-infected patients. Also, this requires shedding the light on the total global cases of ADEM from the annual incidence of dengue. The onset of ADEM can be early or late after dengue infection. Hence, clinicians should pay attention that it can be early or late that patients can forget about their fevers. Moreover, the onset day of neurological manifestations and patients’ temperature were significantly associated with the disease outcome.